The Oxford handbook of international adjudication - Romano, Cesare; Alter, Karen J.; Shani, Yuval; Avgerou, Chrisanthi (Oxford University Press, 2014)
This handbook provides interdisciplinary perspectives on international adjudication, analysing the proliferation of international courts and tribunals from the perspective of both international law and political science. It presents the different theoretical approaches to these courts, their main functions, and the issues confronting them.